Field measurement of ventilation rates. (18th March 2015) - Persily, A. K.
Abstract: Ventilation rates have significant impacts on building energy use and indoor contaminant concentrations, making them key parameters in building performance. Ventilation rates have been measured in buildings for many decades, and there are mature measurement approaches available to researchers and others who need to know actual ventilation rates in buildings. Despite the fact that ventilation rates are critical in interpreting indoor concentration measurements, it is disconcerting how few Indoor Air Quality field studies measure ventilation rates or otherwise characterize the ventilation design of the study building(s). This paper summarizes parameters of interest in characterizing building ventilation, available methods for quantifying these parameters, and challenges in applying these methods to different types of buildings and ventilation systems. These parameters include whole‐building air change rates, system outdoor air intake rates, and building infiltration rates. Tracer gas methods are reviewed as well as system airflow rate measurements using, for example, duct traverses. Several field studies of ventilation rates conducted over the past 75 years are described to highlight the approaches employed and the findings obtained.